KOMITMEN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN BANK bjb CABANG TAMANSARI - Adelia Farhani Romadhona; Ratri Wahyuningtyas (Jurnal Riset Bisnis dan Manajemen, 2019)
This research aims to determine the organizational commitment, organizational culture, and employee performance at Bank BJB Branch Office Tamansari Bandung, and the effect of organizational commitment and organizational culture to the employee performance, both partially and simultaneously. This research uses quantitative method. Data collection technique uses questionnaires distributed to employees of Bank BJB Branch Office Tamansari Bandung, with the population of 160 employees and the samples 115 employees. The sampling technique uses simple random sampling. To interpret the results of the research uses descriptive analysis, correlation analysis, path analysis, and coefficient of determination. The result of data proccessing shows that organizational commitment and organizational culture significantly influence the employee performance at Bank BJB Branch Office Tamansari Bandung, both partially and simultanously.